Analisis Proses Berpikir Siswa dalam Memecahkan Masalah Matematika ditinjau dari Adversity Quotient (AQ) Siswa Kelas VIII MTs Negeri 1 Lombok Barat Tahun Ajaran 2022/2023 - Dahliani, Baiq Mery; Turmuzi, Muhammad; Wahidaturrahmi, Wahidaturrahmi; Azmi, Syahrul (Jurnal Riset Pendidikan Matematika Jakarta, 2023)
This study aims to determine students' thinking processes in solving mathematical problems. Data analysis was carried out based on Ilman's thinking process theory in terms of the students' adversity quotient. This type of research is a qualitative descriptive research. The selection of research subjects was based on the recommendation of the mathematics teacher and obtained class VIII A MTs Negeri 1 West Lombok for the 2022/2023 academic year as research subjects. To deepen the research results, 2 students were selected from each type of AQ students. Data collection techniques using adversity response profile questionnaires, students' thinking process tests and interviews. The data analysis technique used is data reduction, data presentation and conclusion. From the research results it can be seen that climber type students tend to use conceptual thinking processes in solving mathematical problems. Where climber students are able to express what is known and asked in questions with their own sentences, answer with concepts that have been learned and are able to explain the steps taken. Meanwhile, camper students tend to use semi-conceptual thinking processes in solving mathematical problems. Where camper students are able to express what is known and asked in questions, in answering they tend to use concepts that have been learned even though they are incomplete and are less able to explain the steps taken.